Akulturasi Islam Dan Hukum Adat Minangkabau - Asniah, Asniah (AL-ADYAN, 2023)
This research is a qualitative study of Minangkabau customs and culture, data collected by reviewing documents, both in the form of books and articles. In addition, interviews were conducted with a number of Minang figures, and some of the experiences of Minang residents. The results of the study indicate that there has been acculturation between Minang customs and Islamic teachings since the early arrival of Islam in Minang, namely in the 8th century AD. Before the arrival of Islam to the Minangkabau, there were traditions that had been passed down from generation to generation based on their habits. The acculturation that took place was fairly peaceful, so that the traditional leaders did not make a problem at all and accepted it freely in the area. The acculturation of Islam and Minangkabau culture is in the form of syntheticism, while others conform to their teachings. There has been a change when Minang culture and Islam acculturated, namely in three forms. First, when Minang customs are not in line with Islamic law, habituation can be carried out, as contained in the Minang philosophy which reads, "Adaiak basandia alua jo patui', alua jo patui' basandia bana, bana badiri surangnyo" is changed to "Adaiak basandia syara' , syara' basandia Kitabullah”. Second, customs and culture that are in line with Islam are preserved, such as the principle of deliberation and consensus. Third, bring up Islamic da'wah with a new culture that did not exist before, such as the Al-Qur'an khatam ceremony for children.